New Directions in African Education Challenges and Possibilities - Nombuso Dlamini, S. (Africa: Missing Voices, 2007)
It has been said that education in post-colonial Africa is in a state of crisis. Policies and practices from Eurocentric colonial regimes have carried over, intertwining with challenges inherent in the new political and economic climate. Leaders have done little to remedy the malfunctioning education system, and even where attempts have been made, they have overwhelmingly been shaped by commercial and capitalist interests. In New Directions in African Education, Nombuso Dlamini has gathered essays from continental African scholars who, before pursuing graduate studies in North America, had first-hand experience with the education system in post-colonial Africa. Their cross-cultural perspective has provided a unique opportunity to critically examine education in the African context and to present possible courses of action to reinvent its future. These authors are in search of a new model for African education - a model that embraces indigenous knowledge, helps cultivate a greater sense of pride in people of African descent, and, most importantly, serves local needs.